2022
DOI: 10.1007/jhep12(2022)036
|View full text |Cite
|
Sign up to set email alerts
|

Non-minimal coupling of scalar and gauge fields with gravity: an entropy current and linearized second law

Abstract: This work extends the proof of a local version of the linearized second law involving an entropy current with non-negative divergence by including the arbitrary non-minimal coupling of scalar and U(1) gauge fields with gravity. In recent works, the construction of entropy current to prove the linearized second law rested on an important assumption about the possible matter couplings to gravity: the corresponding matter stress tensor was assumed to satisfy the null energy conditions. However, the null energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…It has been shown that one way to investigate the thermodynamic properties of dynamic black holes is working in the limit of weak gravity and considering the non-minimal term as a perturbation around the Einstein gravity, known as the linearized amplitude expansion. [66] In the context of the field equation, we can recast the field equation (35) in a way that the higher order corrections are written as an energy-momentum tensor of geometrical origin describing an effective source term on the right hand side of the standard Einstein field equations, namely…”
Section: Black Hole Thermodynamics and Thermal Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that one way to investigate the thermodynamic properties of dynamic black holes is working in the limit of weak gravity and considering the non-minimal term as a perturbation around the Einstein gravity, known as the linearized amplitude expansion. [66] In the context of the field equation, we can recast the field equation (35) in a way that the higher order corrections are written as an energy-momentum tensor of geometrical origin describing an effective source term on the right hand side of the standard Einstein field equations, namely…”
Section: Black Hole Thermodynamics and Thermal Stabilitymentioning
confidence: 99%
“…It has been shown that one way to investigate the thermodynamic properties of dynamic black holes is working in the limit of weak gravity and considering the non‐minimal term as a perturbation around the Einstein gravity, known as the linearized amplitude expansion. [ 66 ] In the context of the field equation, we can recast the field equation () in a way that the higher order corrections are written as an energy‐momentum tensor of geometrical origin describing an effective source term on the right hand side of the standard Einstein field equations, namely Gμνbadbreak=Tμνmgoodbreak+Tμνg,$$\begin{equation} G_{\mu \nu }=T_{\mu \nu }^{m}+T_{\mu \nu }^{g}, \end{equation}$$where Tμνmbadbreak=8πGYR(R)1YR(R)F2Tμν,$$\begin{equation} T_{\mu \nu }^{m}=\frac{-8\pi G Y_{\mathcal {R}}(\mathcal {R})}{1 - Y_{\mathcal {R}}(\mathcal {R}) {F^2} }T_{\mu \nu }, \end{equation}$$and Tμνg=11YscriptRfalse(scriptRfalse)F2×12[]R1YR(RF2false)gμν+()μνgμν(1YscriptRfalse(scriptRfalse)F2)-0.16em.$$\begin{align} &T_{\mu \nu }^{g}=\frac{1}{1 - Y_{\mathcal {R}}(\mathcal {R}) {F^2} }\nonumber \\ &\;\times{\left[{1 \over 2} {\left[\mathcal {R} - {\left(1 -...…”
Section: Black Hole Thermodynamics and Thermal Stabilitymentioning
confidence: 99%
“…The thermodynamic properties of black holes in higher curvature theories of gravity have been a subject of active research [1][2][3][4][5][6][7][8][9][10][11][12][13]. The area law [14][15][16][17][18] for the entropy of black holes in the presence of higher curvature terms is modified to the Iyer-Wald entropy for stationary black holes [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In previous proofs of the second law [8][9][10], the approach was to fix the JKM ambiguities such that the new entropy functional satisfied a second law. In [11][12][13], building on [8][9][10], a local version of the second law of black hole thermodynamics was established for arbitrary diffeomorphic invariant theories of gravity minimally coupled to matter fields. By local version, we mean one has a local 'entropy current' with non-negative divergence on the black hole's dynamic horizon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation